A Platform Integrating Biophysical and Biochemical Stimuli to Enhance Differentiation and Maturation of Cardiomyocyte Subtypes Derived from Human Induced Pluripotent Stem Cells - Zhonggang Feng; Kota Sawada; Iori Ando; Riku Yoshinari; Daisuke Sato; Tadashi Kosawada (Journal of Cardiovascular Development and Disease, 2025)
To enhance the differentiation and maturation of cardiomyocytes derived from human induced pluripotent stem cells, we developed a bioreactor system that simultaneously imposes biophysical and biochemical stimuli on these committed cardiomyocytes. The cells were cultured within biohydrogels composed of the extracellular matrix extracted from goat ventricles and purchased rat-origin collagen, which were housed in the elastic PDMS culture chambers of the bioreactor. Elastic and flexible electrodes composed of PEDOT/PSS, latex, and graphene flakes were embedded in the hydrogels and chamber walls, allowing cyclic stretch and electrical pulses to be simultaneously and coordinately applied to the cultured cells. Furthermore, a dynamic analysis method employing the transverse forced oscillation theory of a cantilever was used to analyze and discriminate the subtype-specific beating behavior of the cardiomyocytes. It was found that myosin light chain 2v (MLC2v), a ventricular cell marker, was primarily upregulated in cells aggregated on the (+) electrode side, while cardiomyocytes with faint MLC2v but strong cardiac troponin T (cTNT) expression aggregated at the ground electrode (GND) side. mRNA analysis using rtPCR and the gel beating dynamics further suggested a subtype deviation on the different electrode sides. This study demonstrated the potential of our bioreactor system in enhancing cardiac differentiation and maturation, and it showed an intriguing phenomenon of cardiomyocyte subtype aggregation on different electrodes, which may be developed into a new method to enhance the maturation and separation of cardiomyocyte subtypes.